استخدام الطريقة الإيحائية لترقية مهارة الاستماع في تعليم اللغة العربية - Erta Mahyudin Firdaus; Hikmah Hikmah (Jurnal Pendidikan Islam, 2016)
This study aims to test the effectiveness of using suggestopedia method in teaching listening skills for students of Madrasah Al – Hikmah, Malang. The focus of this study was to answer some questions: 1) how is the application of suggestopedia method in listening; 2 ) how is the effectiveness of using suggestopedia method in listening, especially the ability to distinguish stressing an intonation and the ability to understand the Arabic language fragment of reading. It applied quantitative approach with an experimental design by comparing experimental and control class. To gain the data, It applied some techniques, including: observation, interview, doing test (pre and post), and questionnaire. Data collected were analyzed through the following steps: determining test for normality of data, determining test the homogeneity of data, analyzing of the pre-test results, analyzing post-test results, analyzing the results before and after treatment, and a comparing analysis on final results from experimental and control class. The findings show that: (a) The suggestopedia method is appropriate to upgrade students’ skill in listening. (b) it boosts learners’ ability in listening right word for for 2nd eksperimental class is effective but it did not work for 1st class experiment. (c) The impact of suggestopedia method to the students’ ability in discerning word stressing in sentences for both experimental classes is effective. (d) The impact of suggestopedia method used to students’ ability in recognizing script played on audio media in normal speed for both experimental classes is effective.